Angiogenic potential of “Quina do Cerrado” (Strychnos pseudoquina) (Revista Brasileira de Plantas Medicinais, 2024)
Leaf and bark infusions of the Strychnos pseudoquina A.St.-Hil., Loganiaceae, plant have long been used in Brazilian traditional medicine for the treatment of various diseases and medical conditions, showing apparent antipyretic, gastric cicatrizant, and especially antimalarial effects. The literature contains abundant reports of plants that possess bioactive components with therapeutic properties. The search for natural substances that promote or inhibit angiogenesis is the focus of current research, since numerous drugs derived from plants have these effects. Thus, in this study, we investigated the angiogenic potential of S. pseudoquina, using the embryonated chicken egg chorioallantoic membrane assay for the angiogenesis tests. Three concentrations of an aqueous extract of S. pseudoquina bark were tested: 15, 30, and 60 mg/ml. The mean percentages of vascularization of CAMs treated with these three extract concentrations were 15.4%, 17.1%, and 17.2%, respectively, which were significantly higher (p